Bioconjugate techniques - Hermanson, Greg T (Academic Press, 1996)
Bioconjugate Techniques is the essential guide to the modification and crosslinking of biomolecules for use in research, diagnostics, and therapeutics. It provides highly detailed information on the chemistry, reagent systems, and practical applications for creating labeled or conjugate molecules. It also describes dozens of reactions with details on hundreds of commercially available reagents and the use of these reagents for modifying or crosslinking peptides and proteins, sugars and polysaccharides, nucleic acids and oligonucleotides, lipids, and synthetic polymers. Armed with this information and the abundant protocols provided, readers will form unique complexes that can be used for detecting, quantifying, and targeting important analytes. This book helps readers make: high activity antibody-enzymes conjugates, immunotoxins, immunogen complexes, liposome conjugates; as well as biotinylated molecules, avidin or streptavidin conjugates, colloidal gold labeled proteins, PEG or dextran complexes, labeled oligonucleotide probes, and fluorescently tagged or radiolabeled molecules. Key Features* The first book to capture the entire field of bioconjugate chemistry in a single volume* A practical guide to modification and cross-linking technology for research, diagnostics, and therapeutics* Provides useful, detailed, easy-to-follow, step-by-step protocols* Contains easy-to-read and easy-to-understand key concepts for making bioconjugates of all types* Organized to efficiently cover the chemistry of bioconjugation, the major reagents available for modification and cross-linking, and the application of these reagents to the synthesis of highly active conjugates* Cites more than 1200 references keyed to concepts covered in the book* Uses more than 600 figures to illustrate bioconjugate reagents, their reactions, and applications* Suggests sources for all key reagents
Keywords: biologie